Local Bamboo and Earth Construction Potential for Provision of Affordable Structures in Nigeria - NWOKE, OJI ACHUKA; UGWUISHIWU, BONIFACE O (International Journal of Sustainable Construction Engineering and Technology, 2011)
In Nigeria and other developing countries where reinforced concrete in construction is widely used, the high and steadily increasing cost of steel has made construction very expensive. This, coupled with the political will, usually christened “Nigerian Factor” has made any conceived affordable mass housing program by successive governments a mirage. This development has triggered off the search for alternative and suitable replacement for steel reinforcement in concrete works. This search for a cheaper alternative has led to the exploration of abundant, naturally occurring materials such as bamboo, coconut fibres, sisal and oil palm fibres  which can be obtained locally at low cost and low levels of energy using local manpower and technology. The use of these locally available materials as substitute for the conventional materials in reinforced concrete elements can cut construction costs by as much as between 30% and 80%. Interest in these local materials is heightened by the facts that not only are they considered cheap; they are also “eco-friendly”. Also, the rising level of pollution in the construction industry has called for the adoption of “Eco-structures”, which are constructions that are in harmony with the surroundings and do not violate the environment neither through the chosen building materials nor through the construction methods. Several studies  have shown that contemporary  earth construction has the potentials to address the urban housing crisis in the developing countries. On the other hand there is a wrong perception among the users and the professionals that, ‘earth houses are only used by the poor people’. This paper investigates the information available on bamboo and earth material and their possible use as a low cost sustainable building material in Nigeria  in the light of problem of affordable structure. The findings of  this paper shows that more research has to be done to come up with reasonable conclusion. It has however been found that this materials has been used to carryout some of the building activities. Finally the author thinks that if more information is found more can be done to put this materials to use